KETERLAKSANAAN KOMPETENSI PROFESIONAL & PEDAGOGIK MAHASISWA PPL DI JURUSAN PENDIDIKAN MIPA UNIVERSITAS CENDERAWASIH - KOIREWOA, DOLFINA C; RAUNSAY, EDOWARD K (Jurnal Ilmu Pendidikan Indonesia, 2020)
This study aims to provide information about the application of professional competence and pedagogical competence of students in the Department of Science education at the Faculty of teacher training and education at Cenderawasih University. This research is an evaluative study by applying a combination method (mixed method) between quantitative and qualitative data obtained through observation and assessment sheet documents (RPP 1 to 10). The results of this study indicate that the professional and pedagogical competencies have been owned by respondents (PPL students) but each competency has not been fully implemented by PPL students. The results of the analysis show that students who apply professional competence are only 44% or around 19 respondents out of 43 respondents while only pedagogical competencies are 51% or around 22 respondents.